PENGEMBANGAN BERPIKIR KREATIF - Syarifan Nurjan (Universitas Muhammadiyah Ponorogo, 2018)
This study aims to develop students' creative thinking through mind map training by organizing information in learning. Students' thinking skills are needed to understand the subject matter, utilize information and creativity. Thinking is a mental activity in solving problems by distinguishing basic thinking skills and complex thinking skills. Two complex thinking processes namely critical thinking and creative thinking. Critical thinking is an organized process that involves mental activities such as problem-solving, decision making, analyzing assumptions, and scientific inquiry. Creative thinking is a thought process for developing original, aesthetic, constructive ideas or results that relate to views, concepts, and emphasize intuitive, rational, and creative aspects of thinking and synonyms of divergent thinking. The development of students' creative thinking is developing creative thinking, developing a link between mind maps and creative thinking skills, and describing the verses of the Qur'an about creative thinking.